Prevalence of Trapezius Trigger Points in Young Healthy Individuals: Trapezius Trigger Points in Young Healthy Individuals - Khalid, Maria; Arshad, Hafsah; Batool, Fouzia; Khawar Kiani, Sania; Riaz, Huma; Ghafoor Sajjad, Abdul (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
MTrPs are labelled as hard, discrete, and palpable nodules in a taut band of skeletal muscle. It can be further divided into 2 forms, if it is spontaneously painful (i.e., active trigger points) or painful only on compression (i.e., latent trigger points). Objectives: To determine the frequency of active and latent trigger points of trapezius in healthy individuals and to find out its association with gender. Methods: A cross sectional survey was conducted from April 2018-August 2018 after getting approval from the ethical committee of Riphah College of Rehabilitation Sciences. The sample size was 323 which were selected by non-probability (convenient sampling) technique. Data were collected through self-structured questionnaire which also included trigger points assessment form. The data were analyzed using SPSS 24. Results: The mean age of participants was 23.60±4.6years with 60(19.8%) males and 243(80.2%) females. The trapezius trigger point 2 was found more active on right side (TT2Rt side) in 91(30%) and left side (TT2Lt side) 57(18.8%). While the same was more latent in 75(24.8%) on right side (TT2Rt side) and 86(28.4%) on left side (TT2Rt side) among the participants. There was no significant association between active trigger points and gender (p>0.245), as well as the association between latent trigger point and gender was not significant (p>0.740). Conclusions: The frequency of trapezius trigger point is less in healthy individuals whereas the majority of the young individuals have at least one or two active or latent trigger points. There was no significant association of both active and latent trigger points with gender.